Prevalence of complementary and alternative medicine use among rheumatoid arthritis patients in Saudi Arabia - Aseel M. Almuhareb; Tariq M. Alhawassi; Ahmed A. Alghamdi; Mohammed A. Omair; Hussain Alarfaj; Abdulrahman Alarfaj; Bedor A. Alomari; Maysoon S. Alblowi; Haya M. Almalag (Elsevier, 2019)
Background and aim: The use of complementary and alternative medicine (CAM) is unexplored among Saudi rheumatoid arthritis (RA) patients. The aim of this study was to estimate the prevalence and types of CAM used among patients with RA and factors associated with their use. Experimental procedure: A cross-sectional study was conducted at rheumatology clinics in two tertiary hospitals located in Riyadh, Saudi Arabia. The data was collected between May 2017 and February 2018. Unpaired Student's t-tests, Chi-square tests, and Pearson correlation tests were used to compare users vs nonusers. Results: A total of 438 patients (mean age = 49, SD ± 15 years; 89.7% females) were included in this study. Sixty seven percent of included patients had used CAM for their RA. The majority of CAM users were female (92.1%). The most frequently used CAM products were vitamin D (47%), calcium (37%), honey (15%), ginger (13%), turmeric (11%), black seeds (8%), and fenugreek (8%). One hundred ninety-six (45%) patients believe that CAM is safe, and 287 (96%) patients took it because they believed that CAM had "added benefits". Statistically significant differences were found for gender, RA duration, erythrocyte sedimentation rate (ESR) level, and seropositivity between CAM users and nonusers (P = 0.019, P = 0.011, P = 0.022, and P < 0.0001, respectively). A significant correlation was found between the Erythrocyte Sedimentation Rate (ESR) level, RA duration and CAM use (r = 0.110, P = 0.022 and r = 0.121, P = 0.012, respectively). These data indicated that patients who used CAM had higher ESR level and longer disease duration than patients didn't use CAM. Conclusion: There is a high prevalence of CAM use among RA patients. CAM use was perceived to add benefit and patients using it had higher ESR. Larger studies are needed to assess the use of CAM and its impact on RA and its management. Keywords: Chronic illness, CAM practices, Safety, Disease activity